An adaptive reclosing scheme for MVDC distribution networks with mechanical DCCBs. (June 2023) - Cao, Xiaoyong; Wu, Zaijun; Xie, Xingfeng; Quan, Xiangjun; Hu, Qinran; Li, Mingfei
Highlights: A signal injection-based adaptive reclosing scheme reuses the original commutation branch of a mechanical DCCB with a simple control strategy, and thereby the DCCB can be turned into a signal injection source for fault nature identification after fault isolation. The fault nature is identified by measuring the magnitudes of one know frequency of injected voltage signals. Based on the faulty line being isolating reliably, the fault nature is derived before reclosing to avoid a second strike on the network. Simultaneously, fault locations can be calculated under permanent faults with application of this proposed scheme. The performance of the proposed reclosing scheme is compared with the currently used schemes to show its advantages. The scheme is simple in structure and affordable in cost, which makes it possible to popularize its application in MVDC distribution networks. Abstract: The DC distribution network is an effective solution to distributed renewable energy applications. After a fault occurs in the network, it is necessary to quickly identify and isolate it to protect system components. Subsequent to fault isolation by DC circuit breakers (DCCBs), power transmission should be swiftly restored by reclosing to improve system reliability. However, conventional reclosing schemes risk a second strike on the grids and endanger the safety of the networks. Given those drawbacks, an adaptive reclosing scheme for medium-voltage DC (MVDC) networks is proposed in this paper. An additional signal injection branch with a simple control strategy is appended to the existing commutation branch of a mechanical DCCB for reclosing. The fault nature can be identified by analyzing the magnitudes of one know frequency of the voltage signals injected into the faulty lines while fault locations under permanent faults can also be calculated before reclosing by applying this scheme. Compared with currently widely used methods, this scheme is characterized by its simplicity in structure and affordability in costs. Simulation results by PSCAD/EMTDC verify the efficacy and robustness of the proposed scheme.